Identifikasi Bakat Cabang Olahraga Karate menggunakan Metode Australian Sport Search - Anggraeni, Virna; Sagitarius, Sagitarius; Kusdinar, Yopi; Mulyana, Mulyana (Prodi Pendidikan Jasmani dan Olahraga, 2025)
alent identification is a process of detecting an ability systematically, scientifically and measurably. This study aims to determine the potential for talented athletes in the karate sport in children aged 7-12 years through a talent identification test. The sample of this study was 45 boys and girls aged 7-12 years in Bandung Regency. This study is a survey study. The research design used in this study is descriptive quantitative. Talent test data were obtained from 10 test items consisting of anthropometric tests including: height, weight, sitting height and arm length and physical tests including: vertical jump, tennis ball throw and catch, basketball throw, shuttle run, 40 meter sprint and multistage fitness test. To overcome different score units, the data was converted into t-score form then the average was taken then the data was categorized into 5 categories according to the applicable norm formula. The data collection technique used was testing and measurement. The data analysis technique usedwas descriptive analysis with percentage results. So the results of this study are that most of the research subjects are quite talented in the karate sport with a percentage of 40%.